Structure of potamoplankton along a gradient of preservation of riparian vegetation in subtropical streams - PERESIN,DENISE (2014)
Water quality in lotic and lentic systems is greatly influenced by the land use in the adjacent areas. This study was conducted in order to assess whether different degrees of preservation of riparian forest (from well preserved with 30m wide up to degraded with < 5 m wide) influence potamoplankton community structure. The study was conducted in three streams in the upper region of the Rio dos Sinos basin, at four sampling sites, with different width of the forest. Samplings were gathered for abiotic and biological analysis in winter (August 2010) and summer (January/February 2011). The analysis of environmental and biotic variables indicated that seasonality was the main determinant of biomass patterns, regardless of the width of riparian vegetation. The potamoplankton community of the studied streams responded to environmental conditions, although lack of significant difference among the different degrees of riparian vegetation preservation has been observed. Increasing trends on biomass, richness and diversity of species, and higher concentrations of total phosphorus and nitrogen in the non-preserved areas might indicate that the different gradients of preservation of riparian vegetation are related with the water quality in subtropical streams and consequently with the potamoplankton structure.